2000
DOI: 10.1111/1469-7610.00549
|View full text |Cite
|
Sign up to set email alerts
|

Substance Abuse in Young People

Abstract: Adolescent substance abuse, with its heterogeneity, its complexity and its association with behavioural, physical and mental health problems is of increasing interest to many; the politician, the economist, clinicians and researchers, families and young people themselves. Data concerning the prevalence and trends in use of a range of substances in different countries, cultures and different groups are reviewed. The influence of associated mental and physical health problems, the multiple definitions applied to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 315 publications
(297 reference statements)
4
36
0
4
Order By: Relevance
“…Several authors mentioned that learning problems are regularly occurring in individuals with developmental disabilities and mental retardation [15,30,31]. Adolescents with mental disorders and developmental disabilities are attributed a higher risk of emotional and behavioral problems [32][33][34] and substance abuse [35,36] compared with their healthy peers. Moreover, it was found that individuals with learning impairments, emotional and behavioral problems or substance abuse experience significant higher unemployment rates than the general population [37][38][39].…”
Section: Disabil Rehabil Downloaded From Informahealthcarecom By Unimentioning
confidence: 99%
“…Several authors mentioned that learning problems are regularly occurring in individuals with developmental disabilities and mental retardation [15,30,31]. Adolescents with mental disorders and developmental disabilities are attributed a higher risk of emotional and behavioral problems [32][33][34] and substance abuse [35,36] compared with their healthy peers. Moreover, it was found that individuals with learning impairments, emotional and behavioral problems or substance abuse experience significant higher unemployment rates than the general population [37][38][39].…”
Section: Disabil Rehabil Downloaded From Informahealthcarecom By Unimentioning
confidence: 99%
“…We considered several individual, peer and family factors. When searching for relevant literature on illicit drugs we focused on cannabis, as in Finland, like in many developed countries, cannabis products (marijuana, hashish) are the most commonly used ones (Programme on Substance Abuse, 1997; Virtanen and Sjöberg, 2006 (Guxens et al, 2007a(Guxens et al, , 2007bKandel and Yamaguchi, 1993), especially age of onset (Gilvarry, 2000;Vega and Gil, 2005), alcohol consumption (Guxens et al, 2007a(Guxens et al, , 2007b, especially drinking to intoxication Wittchen et al, 2007). Own ever smoking was asked prospectively at the age 14 survey.…”
Section: Predictors-mentioning
confidence: 99%
“…Some individual factors related to leisure time patterns have been earlier suggested as risk factors of cannabis use, such as spending time in bars and discos (Guxens et al, 2007a), delinquency (Tarter et al, 2006), and early age of first sexual intercourse (Poikolainen et al, 2001). Although we included several family factors in the current analyses, there are others which were not considered, such as low parental involvement and higher coercive parental discipline (Chen et al, 2005), tolerance and acceptance of drugs use, poor parental monitoring and family functioning (Gilvarry, 2000). However, when testing our individual predictors among the discordant twin pairs, we actually controlled also for those potential family related factors shared by the twins.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cannabis is the most prevalent illegal substance in most Western countries (Hall et al, 1999;Gilvarry, 2000;Smart and Ogborne, 2000). Cannabis abuse is concentrated in late adolescence and young adulthood (Ellickson et al, 1992;Golub and Johnson, 1994;Chen and Kandel, 1995).…”
Section: Introductionmentioning
confidence: 99%